AN ANALYSIS OF PEDAGOGICAL GESTURE PERFORMED BY NOVICE TEACHER IN TEACHING ENGLISH - Intan, Nurmala; Budiharto, Raden Agus (The Ellite of Unira, 2025)
Gestures are one technique commonly used by teachers in delivering material. This study aims to investigate types of gestures as well as the benefits of using them that are used by novice teachers in teaching English and in the learning process. This research is a qualitative descriptive study that examines novice teachers from different schools. It takes four observations for each class. From the research conducted, this study resulted in four types of gestures generally used and five benefits for novice teachers and also three benefits for students. The types of hand gestures are deictic, iconic, metaphor, and beat gesture. While the benefits of using gestures are that teachers can easily clarify their ideas in explaining some difficult vocabulary, it can also help students understand the materials easily, and it reduces their nervousness toward the students and allows them to enjoy the class. This study is hoped to be able to provide insight to teachers about the importance of using gestures in learning English by considering the benefits.